Penerapan Data Driven Decision Making dalam Perspektif Pemilik dan Operator Kapal - Wahyu, Marsellinus Bachtiar (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
The maritime industry’s crucial role in the global economy is vital, serving as the lifeline for the distribution of commercial goods worldwide. Data-Driven Decision Making (DDDM) in the maritime sector has the potential to be a game changer. By utilizing data obtained from sensors, communication tools, and integrated systems, operators can optimize fleets, improve fuel efficiency, and enhance maintenance scheduling. From the perspective of ship owners/operators, decisions regarding scheduling, operations, docking, and crew management are prioritized to ensure company profitability. Current business practices necessitate exploring the benefits of using DDDM in decision-making for ship owners/operators. The use of Big Data and DDDM approaches offers advantages such as cost efficiency and improved fleet performance. Data collection and analysis in the maritime sector include various methods, such as Automatic Identification Systems (AIS), weather data, and onboard sensor equipment. Implementing DDDM presents several challenges from the perspective of ship owners/operators, including data quality and availability, system integration, high implementation costs, regulatory compliance, and resistance to change.